2010
DOI: 10.1111/j.1558-5646.2010.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

REDUCED GENE FLOW AT PERICENTROMERIC LOCI IN A HYBRID ZONE INVOLVING CHROMOSOMAL RACES OF THE HOUSE MOUSEMUS MUSCULUS DOMESTICUS

Abstract: The West European house mouse, Mus musculus domesticus, is a particularly suitable model to investigate the role of chromosomal rearrangements in reproductive isolation. In fact, it exhibits a broad range of chromosomal polymorphism due to Robertsonian Chromosomal rearrangements (e.g., deletions, inversions, centromeric fusion or fissions) are extensively studied events known to result in various karyotypes in natural populations of plants and animals (White 1978;Rieseberg and Willis 2007).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 64 publications
5
58
1
Order By: Relevance
“…Results for this analysis of Italian mice with our set of loci (F ST ¼ 0.404; 95% confidence interval (CI): 0.308-0.487) are clearly similar to those obtained by Panithanarak et al (2004) and confirm that the degree of differentiation observed for the Madeiran metacentric mice is not because of some property of the particular microsatellites used in this study. This is further supported by the observed degree of differentiation between localities in Portugal (F ST ¼ 0.287; 95% CI: 0.249-0.326), Scotland (F ST ¼ 0.225; 95% CI: 0.158-0.301) and Spain (F ST ¼ 0.149; 95% CI: 0.106-0.189), which is in the same range as previous studies (Dallas et al, 1995(Dallas et al, , 1998Panithanarak et al, 2004;Franchini et al, 2008Franchini et al, , 2010.…”
Section: Relationship Of Madeiran Metacentric Mice With Those Of Elsesupporting
confidence: 78%
See 2 more Smart Citations
“…Results for this analysis of Italian mice with our set of loci (F ST ¼ 0.404; 95% confidence interval (CI): 0.308-0.487) are clearly similar to those obtained by Panithanarak et al (2004) and confirm that the degree of differentiation observed for the Madeiran metacentric mice is not because of some property of the particular microsatellites used in this study. This is further supported by the observed degree of differentiation between localities in Portugal (F ST ¼ 0.287; 95% CI: 0.249-0.326), Scotland (F ST ¼ 0.225; 95% CI: 0.158-0.301) and Spain (F ST ¼ 0.149; 95% CI: 0.106-0.189), which is in the same range as previous studies (Dallas et al, 1995(Dallas et al, , 1998Panithanarak et al, 2004;Franchini et al, 2008Franchini et al, , 2010.…”
Section: Relationship Of Madeiran Metacentric Mice With Those Of Elsesupporting
confidence: 78%
“…Previous studies in house mice involving chromosomally less divergent races typically show higher levels of genetic differentiation at microsatellite loci (F ST ¼ 0.39, 13 microsatellite loci (Panithanarak et al, 2004); F ST ¼ 0.187, 8 microsatellite loci (Franchini et al, 2008); F ST ¼ 0.133, 12 microsatellite loci (Franchini et al, 2010)). More pronounced differentiation has also been recorded in a study involving metacentric and standard karyotype (all-acrocentric) mice (F ST ¼ 0.29; eight microsatellite loci (Dallas et al, 1998)), as well as between standard karyotype mice, even in localities only 300 m distant from one another (F ST ¼ 0.18; six microsatellite loci (Dallas et al, 1995)).…”
Section: Relationship Of Madeiran Metacentric Mice With Those Of Elsementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a differential effect on gene flow of hybrid breakdown vs reduced proximal recombination is expected. This suggests that (i) both recombination reduction and hybrid unfitness act synergistically to modify the gene flow landscape between chromosomal races of the house mouse as previously stated (Panithanarak et al, 2004;Franchini et al, 2010;Gimenez et al, 2013), and (ii) the effect of hybrid unfitness is expected to increase with the degree and type of heterozygosity. Combining simulation approaches with analyses, using high resolution genomic markers in wild populations, will undoubtedly assist in teasing apart the respective contribution of both factors, and further refine the expected patterns of divergence related to Rb fusions.…”
Section: Effect Of Rb Heterozygosity On Gene Flowmentioning
confidence: 79%
“…However, several studies have addressed this question by measuring the level of divergence of mapped microsatellite markers between chromosomally differentiated house mice. In all cases, centromeric loci exhibited higher differentiation levels than distal ones, regardless of the type of meiotic heterozygosity of the hybrids, that is, complex chains or rings (Panithanarak et al, 2004;Förster et al, 2013;Gimenez et al, 2013 ) or trivalents (Franchini et al, 2010). Previous studies have indicated that recombination suppression extended up to 15-20 cM from the centromere depending on the chromosomes involved in the Rb fusion and the genetic background (Davisson and Akeson, 1993;Gimenez et al, 2013;Capilla et al, 2014).…”
Section: Effect Of Rb Heterozygosity On Gene Flowmentioning
confidence: 99%